THE IMPACT OF ZAKAT INFAQ SHADAQAH IN THE EMPOWERMENT OF DHUAFA IN THE SURABAYA CITY - Trigatra Akbar Utama El Yanda; Siti Inayatul Faizah (Universitas Airlangga, 2020)
This study aims to determine the impact of the utilization of zakat infaq shadaqah funds at LAZISMU Surabaya to empowerment the poor community. The Impact is measured by indicators of success and failure of business, success and failure of empowerment, and welfare of the perspective of maqashid sharia. Those indicators were measured from before and after mustahik received assistance from LAZISMU Surabaya. The method used is qualitative-descriptive with case study methods. The results of this study are that there informants/mustahik who experienced better changes and did not experience better changes than before. Positive change can be measured by the indicators of success, while the cause of the failure is considered with the failure factors described above.Keywords: Impact, Zakat Infaq Shadaqah, Utilization, EmpowermentREFFERENCE Sasono et. al. (1998). Solusi Islam atas problematika umat: Ekonomi, pendidikan dan dakwah. Jakarta: Gema Insani Press.Ali, Mohammad Daud. (1998). Sistem ekonomi Islam zakat dan wakaf. Jakarta: Universitas Indonesia.Bariadi, Lili., et all. (2005). Zakat dan wirausaha. Jakarta: Centre For Entreneurship Development.Chaudhry, Muhammad Sharif. (Tanpa Tahun). Sistem ekonomi Islam: Prinsip dasar. Terjemahan oleh Suherman Rosyidi. 2012. Jakarta: Kencana Prenada Media Group.Gaus Ahmad. (2008). Filantropi dalam masyarakat Islam. Jakarta: PT Elex Media Komputindo.Kartasasmita. (1996). Pembangunan untuk rakyat: Memadukan pertumbuhan dan pemerataan. Jakarta: CIDES.Khasanah, Umrotul. (2010). Manajemen zakat modern. Malang: UIN Maliki Ibrahim Press.Mujahidin, Akhmad. (2007). Ekonomi Islam. Jakarta: PT. Raja Grafindo Press.Ryandono, Muhammad Nafik Hadi,. Muhammad. (2008). Ekonomi ZISWAQ (Zakat, Infak, Sedekah dan Wakaf). Surabaya: IFDI dan Cenforis.Ryanti, Benedicta. (2003). Kewirausahaan dari sudut pandang psikologi kepribadian. Jakarta: Grasindo.Sanrego, D. Yulizar & Moch Taufik. (2016). Fikih tamkin (fiqih pemberdayaan). Jakarta: Qisthi Press.Sarwat, A. (2014). Seri fiqih kehidupan zakat. Kuningan: Rumah Fiqih Publishing.Shieddieqy, Hasbi. (2005). Panduan zakat. Semarang: Hayam Wuruk.Sugiyono. (2015). Memahami penelitian kualitatif. Bandung: Alfabeta.Suryana. (2003). Kewirausahaan. Jakarta: Salemba Empat.Tjiptoherianto et. al. (1988). Islam dan kemiskinan. Bandung: Penerbit Pustaka.Widiastuti, T. (2016). Model pendayagunaan zakat produktif oleh lembaga zakat dalam meningkatkan pendapatan mustahiq. Jurnal Ekonomi Dan Bisnis Islam, 1(1), 89–102.Widjaja, HAW. (2003). Otonomi desa. Jakarta: PT Raja Grafindo Persada.W. J. S. Poerwadarminta. (1999). Kamus umum bahasa Indonesia. Jakarta: Balai Pustaka.Yasa IGWM. (2008). Penanggulangan kemiskinan berbasis partisipasi masyarakat di Provinsi Bali. Input: Jurnal Ekonomi dan Sosial, 1(2), 86-91.Yunus, Hadi Sabari. (1989). Subject matter dan metode penelitian geografi permukiman kota. Yogyakarta: Fakultas Geografi Universitas Gadjah Mada.Yin, Robert. K. (2009). Studi kasus; Desain dan metode. Jakarta: Raja Grafindo Persada.Zimmerer et. All. (2009). Essential of entrepreneurship and small bisiness management: Kewirausahaan dan manajemen usaha kecil, Edisi 5, Terjemahan Deny Arnos Kwary. Jakarta: Salemba Empat.